Implications of Mixed Marriage on the Probability of Murder in the Perspective of Law and Human Rights - Maharani, Aulia; Dewi, Vika Puspita; Maharani, Diva Alya; Ningrum, Lia Widya; Hamdani, Mushfiq (Jurnal Scientia Indonesia, 2021)
This article examines the legality of mixed marriages in the context of different nationalities in terms of positive law in Indonesia and legal problems regarding mixed marriages where in fact every human being has the right to live in a family by holding the marriage. However, the validity of the marriage will be a dilemma because of differences in citizenship which often have an impact on the rights between the two, even in this case a crime is murder. For this reason, the purpose of this paper is to find out the regulations in solving these problems by prioritizing law and human rights in order to create order and justice. The writing of this article uses normative law with a statutory approach and a case approach. The results of the study found that there were indicators of legal problems between husband and wife who had mixed marriages in the context of different nationalities. And the state's obligation to protect, respect, uphold and promote human rights and the enforcement of just law. So there are important things that need to be considered if there are Indonesian citizens who want to marry foreign nationals.